Pembuatan Sambal Petis Udang Instan Bubuk Menggunakan Teknik Foam-Mat Drying Dengan Penambahan Maltodextrin - Maulana Dzaky Hiba Dillah Akbar; Niken Purwidiani; Ila Huda Puspita Dewi; Mauren Gita Miranti (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Shrimp petis chili sauce is a chili sauce made from shrimp petis paste added with maltodextrin. The manufacture of instant shrimp chili powder uses the foam-mat drying technique , which in this method requires a foam binding agent and stabilizer, namely maltodextrin. The purpose of this study is to find out: 1) the sensory quality of chili sauce petis instant shrimp powder and rehydration from the addition of maltodextrin by 5%, 10%, 15%; 2) nutritional content of chili sauce, petis, instant shrimp powder and rehydration; and 3) the selling price of chili sauce petis instant shrimp powder. This type of research is an experimental research, which is tested on 30 panelists. Sensory quality results were analyzed using a single anova of the SPSS program, the nutritional content was analyzed in the laboratory, and the selling price was analyzed using conventional methods. The results of data analysis showed: 1) the best treatment from the results of the sensory quality test was the addition of maltodextrin as much as 5% with the average result in chili sauce of powdered shrimp chili sauce 4.47, aroma 4.43, texture 3.83. In chili petis rehydration color 4.60, aroma 4.67, taste 4.67, viscosity 4.47, overall preference 4.57; 2) The results of laboratory tests on chili sauce instant shrimp powder and rehydration were vitamin A powder 62.8mg/100g, rehydration 88.5mg/100g, water content of powder 11.36%, rehydration 26.10%, ash content of powder 3.80%, rehydration 2.60%, salt content of powder 2.81%, rehydration 2.42%, protein content of powder 56.10%, rehydration 41.06%; and 3) the selling price of packaged instant shrimp powder chili sauce weighing 30g is Rp 4,000.